Applicability of PEF methodologies in comparison of LCAs of different food products in Nordic countries - Hietala, Sanna; Kristensen, Troels; Woodhouse, Anna; Ahlgren, Serina; Mogensen, Lisbeth (Nordic Council of Ministers, 2023)
The European Commission has published Product Environmental Footprint (PEF) guidelines to promote a harmonised product group-specific environmental footprint assessment. The need for harmonised methods in environmental footprint assessment has arisen from increasing number of green claims used especially in marketing of products. There has been a growing desire to communicate the environmental footprints of food products, but in the absence of well-established, standardised assessment guidelines, green claims have been made on variable grounds. The PEF method developed by European Commission is based on Life Cycle Assessment (LCA) and the current 16 environmental impact categories included are relying on scientifically sound impact assessment methods that are agreed at international level. While the harmonised methods of Product Environmental Footprint Category Rules (PEFCRs) are suitable for assessment of environmental impacts of products and for comparison of performance of products from the same category, comparability across different categories has not been the objective. Based on previous results and ongoing work, the main objective for the work reported here, has been to investigate to what extent the LCAs conducted with the PEF methodologies provide comparability even between product categories and will provide insights from a Nordic perspective. The review was conducted by comparing the PEFCRs and the general PEF guidance in parallel, per life cycle stage, to find deviations especially between different PEFCRs. General PEF guideline consisted of the Commission recommendations and the guidance given in Annexes. Previous studies were utilised here as a basis together with the PEF method and guidance documentation, for summarising the relevant differences and coherence in collecting inventory data, requirements for modelling, utilised emission factors (EF), system boundaries, allocation approach and functional units (FU). The transition phase PEFCRs were reviewed in order to find coherence or discrepancies in strictness regarding data quality requirements. The revised Recommendation by European Commission was included to some extent, in a more general level. For the evaluation of the potential differences in LCA results of products assessed with the PEF method, the application of PEFCR of dairy products in the Nordic countries (Denmark, Finland, Norway, Sweden) was analysed in more detail, focusing on the largest contribution to global warming potential, i.e., methane from enteric fermentation. In overall, it was seen that PEF method is promoting comparability and the given guidance increases consistency, transparency, and reliability of the conducted studies. Yet, many aspects discussed in the report remain unsolved and need more careful considerations in forthcoming PEF studies and PEFCR guidance’s if comparisons across product categories are made. Raised issues were regarding functional unit, system boundaries, allocation, manure handling and use stage modelling. Prior to utilising PEF method in comparison of product LCAs, harmonisation of these issues should be conducted across PEFCRs. In the case of estimating the product footprint across countries, the use of different National Inventory Report (NIR) assessment models, here illustrated by enteric methane, was found problematic as the level of emission potentially change due to the model parameters and not because of the production data. The used NIR assessment models should be validated for fair comparison. This problem is already existing in PEF methods, when comparison is conducted within a product group and by following PEFCRs. The use of national assessment models is problematic, even in the case that they are approved by IPCC as they are not validated for comparison.
Keywords: life cycle analysis; environmental impact assessment; environmental footprint; PEFCR; PEF; Product Environmental Footprint; Food products; Nordic